(untitled) - Bùi, Minh Châu (Can Tho, 2010)
It provides students with the theory of how to read efficiently as well as opportunities to practice reading skills. The goal of this course is to familiarize students with reading skills through intensive readings.
Keywords: English language,Reading comprehension,Anh ngữ thực hành,Kỹ năng đọc hiểu